First look into the venom of Roatan Island's critically endangered coral snake Micrurus ruatanus: Proteomic characterization, toxicity, immunorecognition and neutralization by an antivenom - Lippa, Enikő (2019)
A proteomic and toxicological study of the venom from one specimen of Micrurus ruatanus, a critically endangered coral snake species endemic to Roatan Island, Honduras, was carried out. Immunorecognition and neutralization of venom lethality by an anticoral antivenom was also evaluated. Forty peaks were collected from RP-HPLC fractionation of the venom. After SDS-PAGE analysis, fifty-eight bands were examined by MALDI-TOF/ TOF mass spectrometry. Micrurus ruatanus venom displayed a three-finger toxin (3FTx)-rich venom phenotype, as well as a significant amount of phospholipases A2 (PLA2s). Various other proteins were identified, including Kunitz-type inhibitor proteins, L-amino acid oxidases, C-type lectin/lectin-like, metalloproteinases, serine proteinases, vespryn/ohanin, 5′-nucleotidases, glutathione peroxidases, and phosphodiesterases. Micrurus ruatanus venom displayed significant PLA2 activity in vitro and myotoxicity in vivo. The venom showed high lethal potency in mice, being one of the most lethal in Central America. The anticoral antivenom (SAC-ICP) produced by Instituto Clodomiro Picado neutralized the lethal activity of the venom. Major fractions with relevant lethal activity were also identified by a screening analysis. Significance: The proteomic characterization, toxicity, immunorecognition and neutralization of Micrurus ruatanus venom have been determined for the first time. This coral snake is endemic to Roatan Island and contains a three-finger toxin-rich venom that displayed a potent lethal activity in mice. The anticoral antivenom produced by Instituto Clodomiro Picado neutralized the lethal activity of this venom in vivo, and therefore should be effective in the treatment of envenomings by this snake.